1997
DOI: 10.4049/jimmunol.159.10.5084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical deformation promotes secretion of IL-1 alpha and IL-1 receptor antagonist.

Abstract: Both IL-1 alpha and IL-1 beta lack an N terminus secretory sequence, and the mechanism of secretion of these pleiotropic cytokines is incompletely understood. The epidermis contains large quantities of IL-1 alpha in keratinocytes, which may play a role in inducing endothelial adhesion molecules and promoting extravasation of leukocytes. Here we report that mechanical deformation of human keratinocytes leads to rapid release of IL-1 alpha, possibly through transient disruptions in the plasma membrane. Using a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…VEGF is known to play a role in the later angiogenic phase of wound healing, but there are several studies showing an immediate secretion of the growth factor as a consequence of skin-barrier disruption [33][34][35], which is corroborated by the present study. The proinflammatory cytokine IL-1α is prestored in keratinocytes and serves as an acute damage signal [36,37]. This is reflected by the increasing dialysate concentrations of IL-1α observed in this study after mechanical disruption of the skin barrier.…”
Section: Discussionmentioning
confidence: 61%
“…VEGF is known to play a role in the later angiogenic phase of wound healing, but there are several studies showing an immediate secretion of the growth factor as a consequence of skin-barrier disruption [33][34][35], which is corroborated by the present study. The proinflammatory cytokine IL-1α is prestored in keratinocytes and serves as an acute damage signal [36,37]. This is reflected by the increasing dialysate concentrations of IL-1α observed in this study after mechanical disruption of the skin barrier.…”
Section: Discussionmentioning
confidence: 61%
“…Generally, IL-1α is particularly abundant in the cytokine profile of activated macrophages, neutrophils, epithelial cells, and endothelial cells. Keratinocytes, in particular, release large amounts of IL-1α following tissue injury or stress-related stimuli [ 51 , 52 ]. The transcription factors AP1 and NF-κB can also induce IL-1α expression in a cell-type-specific manner [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the use of the new extraction protocol, we were able to quantify low‐abundant cytokines, such as IL‐8 and G‐CSF that could provide a classification of damaged skin from healthy skin 22 . It is well known that a variety of skin insults (mechanical, chemical and thermal) alters the production of the high‐abundant cytokines, namely, IL‐1α and IL‐1RA 12 . In addition, each of the low‐abundant cytokines plays a unique role in maintaining the barrier function, for example, TNF‐α, INF‐γ and IL‐1β are important in lipid synthesis, whereas IL‐8 and G‐CSF are associated with dendritic cell migration and neutrophil regulation 35‐37 .…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes in the skin layer play a major role in the inflammatory processes by the production of signalling molecules, namely, cytokines and chemokines. Previous in‐vitro studies, involving cell and tissue models, and animal studies have reported the release of cytokines following prolonged mechanical loading 12,13 . Non‐invasive adhesive tapes have been used to sample cytokines typically IL‐1α, IL‐1RA, IL‐8, INF‐γ, and IL‐6 from sebum on the skin surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation